Null scrolls in the 3-dimensional Lorentzian space - Balgetir, Handan; Bektaş, Mehmet; Ergüt, Mahmut (Balkan Society of Geometers, 2003)
In this study, a timelike ruled surface in the 3 - dimensional Lorentzian space ?13 which is called null scroll is generated by a null straight line which moves along a null curve with respect to the null frame. In a null scroll, the central point, the curve of striction, pseudo-orthogonal trajectory and some theorems related to these structures are obtained in the 3-dimensional Lorentzian space ?13. Results about developable null scrolls are provided as well.
Keywords: Lorentzian space; Null curve; Null scroll